2020
DOI: 10.1093/ckj/sfaa051
|View full text |Cite
|
Sign up to set email alerts
|

Trends in assisted peritoneal dialysis over the last decade: a cohort study from the French Peritoneal Dialysis Registry

Abstract: Background There is limited information available on the use of assisted peritoneal dialysis (PD) over time and the impact of economic incentives on its utilization. The aim of this study was to describe the trends in assisted PD utilization and the type of assistance provided. We wanted to estimate if an economic incentive implemented in 2011 in France was associated with an increase in the utilization of nurse-assisted PD. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 37 publications
1
13
0
2
Order By: Relevance
“…The worsening over time of transfers to HD due to catheter issues in family-assisted PD patients could reflect a decrease in caregivers’ involvement. A preceding study by our team found a linear decline in family-assisted PD use over time, notably among others, because of a modification in the state of caregivers’ health [48]. Catheter complications, a leading cause of early PD cessation [8, 14, 44], have been acknowledged as an important consideration by patients and healthcare professionals [33].…”
Section: Discussionmentioning
confidence: 99%
“…The worsening over time of transfers to HD due to catheter issues in family-assisted PD patients could reflect a decrease in caregivers’ involvement. A preceding study by our team found a linear decline in family-assisted PD use over time, notably among others, because of a modification in the state of caregivers’ health [48]. Catheter complications, a leading cause of early PD cessation [8, 14, 44], have been acknowledged as an important consideration by patients and healthcare professionals [33].…”
Section: Discussionmentioning
confidence: 99%
“…Une descriptiion du fontionnement du RDPLF a été publiée il y a quelques années [1], et différents travaux portant sur les modules optionnels ont été publié récemments [2][3][4][5][6][7][8][9] aux quels nous rennvoyons le lecteur. Le but de cet article est de faire une synthèse des résultats bruts observés dans le module principal en 2020 et de susciter, à partir de là, de futurs travaux plus élaborés.…”
Section: Introductionunclassified
“…29,30 Additionally, in the coming ageing society, nurses' role in assisted PD will be of much more importance. 31 The present study has several limitations that need to be acknowledged. First, due to the retrospective observational design of this study and the causality between the submission rate and patients' clinical outcomes, we could not know whether the increase in the submission rate leads to improvement in patients' clinical outcomes.…”
Section: Discussionmentioning
confidence: 90%
“…Training based on principles of adult education and the experience of PD nurses are aspects of a successful PD programme 29,30 . Additionally, in the coming ageing society, nurses' role in assisted PD will be of much more importance 31 …”
Section: Discussionmentioning
confidence: 99%